PERCEPCIONES DE ESTUDIANTES UNIVERSITARIOS SOBRE LA PLANIFICACIÓN DE LA ESCRITURA - Gallego Ortega José Luis; Antonio García Guzmán; Antonio Rodríguez Fuentes (European Scientific Journal, ESJ, 2014)
This paper includes a research whose principal objective was to know the Teaching College Students’ perception about their competence to planning the writing text. This study involved to fourteen students, aged between 20.1 and 23.1 years old (mean 21.3). All of them were finishing the 2nd year of degree in Primary Education. A qualitative research (case study), with exploratory character was designed to carry out this study using the "cognitive interview" as a strategy for data collection and the "content analysis” to interpret them. For this, a category system valued by the procedure of “expert judgment” was created. The results reveal that, in general, the university students use strategies that facilitate the process of planning on writing, to a greater or lesser degree depending on the case. However, the recording and ordination of ideas in the text, as well as the textual organization were the cognitive operations in which the biggest problems were identified.